Experimental investigation on lightweight rubberized concrete beams strengthened with BFRP sheets subjected to impact loads - Pham, Thong; Chen, Wensu; Elchalakani, M.; Karrech, A.; Hao, Hong (ELSEVIER SCI LTD, 2020)
This study experimentally investigates the impact behaviour of rubberized concrete beams strengthened with basalt fiber reinforced polymer (BFRP). Twelve reinforced concrete beams, which consisted of different rubber contents (0%, 15%, and 30%), were tested under impact loads. Various wrapping schemes were considered to determine the most effective strengthening schemes for impact resistance performance of both the conventional and rubberized concrete beams. The experimental results have shown that rubberized concrete had 10–18% higher imparted energy per unit weight than that of normal concrete. The rubberized concrete beams localized the damage at the impacted area and slowed down the stress wave velocity. Although rubberized concrete materials possessed lower compressive strength (50.3 MPa, 25.4 MPa and 14.7 MPa for concrete with 0%, 15% and 30% rubber content, respectively), they yielded less displacement as compared to the reference beams under the same impact. The rubberized concrete beams experienced a lower peak impact force under the same impact. Meanwhile, the use of U-shape BFRP wraps concentrating at the impacted area showed similar performance as those with BFRP wraps uniformly distributed along the entire beam, therefore, this proposed strengthening scheme provides a cheaper solution for strengthening concrete structures.